Gamma and fast neutrons flux radiation minimization during the concentrated flux formation of delayed neutrons - Gokov, S.P.; Karpus, S.H.; Kasilov, V.I.; Kovalenko, G.D.; Kochetov, S.S. (Problems of Atomic Science and Technology, 2023)
The concept of a concentrated neutron flux shaper for neutron capture therapy of cancer has been developed. A technique for two stage minimization of the accompanying fast neutron flux and gamma radiation background during the formation of a delayed therapeutic neutron flux is discussed. A variant of the shaper design of epithermal neutrons based on the use of collimators directed from a part of the spherical surface along the radius to the center to concentrate the flux density of these neutrons on the irradiated object is proposed. Розроблено концепцію формувача концентрованого потоку уповільнених нейтронів для нейтрон захватної терапії раку. Обговорюється методика двоступінчаcтої мінімізації супутнього фона швидких нейтронів та гамма випромінювання при формуванні уповільнених терапевтичних потоків нейтронів. Запропоновано варіант конструкції формувача епітеплових нейтронів на основі використання коліматорів, які спрямовані з частин сферичної поверхні по радіусу до центрa для концентрування густини потоку цих нейтронів на об’єкті, що опромінюється.